Lot of Square roots

Level pending

find 2 + 2 + 2 + 2 + . . . 2 + \sqrt{2 + \sqrt{2 + \sqrt{2 + ...}}}

3 2 4 1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let 2 + 2 + 2 + 2 + . . . = x 2+ \sqrt{2 + \sqrt{2 + \sqrt{2 + ...}}} = x
Next, subtract 2 2 from both sides and square both sides, the equation becomes:
2 + 2 + 2 + 2 + . . . = ( x 2 ) 2 2+ \sqrt{2 + \sqrt{2 + \sqrt{2 + ...}}} = (x-2)^{2} .
Notice how the left side becomes x x again, and by substituting on the left side and distributing on the right side, we get the following equation:
x = x 2 4 x + 4 x= x^{2} - 4x +4
x 2 5 x + 4 = 0 x^{2} -5x +4 =0
( x 4 ) ( x 1 ) = 0 (x-4)(x-1)=0 so x = 1 , 4 x= {1,4} .
Obviously, the answer must be greater than 2 2 because the first term is 2 2 and we're adding positive values. Knowing that x must be greater than 2 2 , we can eliminate 1 1 from the solution set and that leaves us with the final answer: 4 \boxed{4} .

Kevin Mo
Apr 19, 2014

Move the 2 over to form 2 + 2 + 2 + . . . = 2 \sqrt{2+\sqrt{2+\sqrt{2+...}}} = -2 and square both sides ( 2 + 2 + 2 + . . . ) 2 = ( 2 ) 2 (\sqrt{2+\sqrt{2+\sqrt{2+...}}})^{2} = (-2)^{2} . What you will get is 2 + 2 + 2 + 2 + . . . = 4 2 + \sqrt{2+\sqrt{2+\sqrt{2+...}}} = 4 , which is what we want. Thus our answer is 4 Ans. \boxed{4} \textbf{ Ans.}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...